1996
DOI: 10.1183/09031936.96.09061240
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilatory support does not facilitate recovery from acute respiratory failure in chronic obstructive pulmonary disease

Abstract: This investigation evaluates, in a prospective, randomized and controlled manner, whether noninvasive ventilatory support (NIVS) with bilevel positive airway pressure (BiPAP) facilitates recovery from acute respiratory failure (ARF) in patients with chronic obstructive pulmonary disease (COPD).Twenty four patients (mean age (±SEM) 68±2 yrs) with COPD (forced expiratory volume in one second (FEV1) at discharge 33±2% predicted), who attended the emergency room because of ARF (pH 7.33±0.01; arterial oxygen tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
1
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(117 citation statements)
references
References 21 publications
4
98
1
12
Order By: Relevance
“…Firstly, indications for NIPPV still are ill defined, mostly in patients with mild and moderate acidosis who represent by far the majority of those admitted to a regular medical ward or to a Division of Respiratory Diseases. Indeed, at variance with the previously quoted authors, [4,5], BARBE Â et al [6] found that NIPPV administered for 6 h a day during the first 3 days of hospitalization does not facilitate recovery from ARF in such patients; likely, FOGLIO et al [7] demonstrated that NIPPV for 4 h a day for five consecutive days a week for 3 weeks does not have a better result than standard therapy alone. Furthermore, the effect of late treatment with NIPPV after an acute exacerbation in terms of patients' survival, need for further hospital admissions or need for invasive mechanical ventilation is not fully known, though CON-FALONIERI et al [8] demonstrated an improvement in the long-term outcome of a group of patients treated with NIPPV compared to a group of historically matched control patients treated conventionally.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…Firstly, indications for NIPPV still are ill defined, mostly in patients with mild and moderate acidosis who represent by far the majority of those admitted to a regular medical ward or to a Division of Respiratory Diseases. Indeed, at variance with the previously quoted authors, [4,5], BARBE Â et al [6] found that NIPPV administered for 6 h a day during the first 3 days of hospitalization does not facilitate recovery from ARF in such patients; likely, FOGLIO et al [7] demonstrated that NIPPV for 4 h a day for five consecutive days a week for 3 weeks does not have a better result than standard therapy alone. Furthermore, the effect of late treatment with NIPPV after an acute exacerbation in terms of patients' survival, need for further hospital admissions or need for invasive mechanical ventilation is not fully known, though CON-FALONIERI et al [8] demonstrated an improvement in the long-term outcome of a group of patients treated with NIPPV compared to a group of historically matched control patients treated conventionally.…”
contrasting
confidence: 51%
“…Patients with mild and moderate ARF are usually deemed to be at lower risk and, accordingly, are treated with medical therapy alone. Such physician behaviour has been reinforced by the recent demonstration by BARBE Á et al [6] that NIPPV does not improve early mortality and need for ET intubation in such patients. However, BARBE Á et al [6] did not follow their patients after hospital discharge, a period during which the current authors could demonstrate a better survival rate and a lower incidence of new hospital admissions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The most relevant was a multicentre trial on COPD exacerbation that confirmed the efficacy of NIV in this setting (21 (22).…”
Section: Conventional Wardsmentioning
confidence: 99%
“…Nevertheless, this method of ventilation requires the presence of nurses familiar with the technique, and this may be time-consuming [3,8]. Moreover, according to certain reports [2,4,9,10], some patients do not tolerate noninvasive ventilatory support, and side-effects of these techniques occur quite frequently [3,11].…”
mentioning
confidence: 99%